Synthesis, and docking studies of phenylpyrimidine-carboxamide derivatives bearing 1H-pyrrolo[2, 3-b]pyridine moiety as c-Met inhibitors. Issue 8 (15th April 2016) - Zhu, Wufu; Wang, Wenhui; Xu, Shan; Wang, Jianqiang; Tang, Qidong; Wu, Chunjiang; Zhao, Yanfang; Zheng, Pengwu
Graphical abstract: Abstract: Four series of phenylpyrimidine-carboxamide derivatives bearing 1 H -pyrrolo[2, 3- b ]pyridine moiety (14a –e, 15a –g, 16a –e and17a –g ) were designed, synthesized and evaluated for the IC50 values against three cancer cell lines (A549, PC-3 and MCF-7). Four selected compounds (15e, 16a –b and17a ) were further evaluated for the activity against c-Met kinase, HepG2 and Hela cell lines. Most of the compounds showed excellent cytotoxicity activity and selectivity with the IC50 valuables in single-digit μM to nanomole range. Eleven of them are equal to more active than positive control Foretinib against one or more cell lines. The most promising compound15e showed superior activity to Foretinib against A549, PC-3 and MCF-7 cell lines, with the IC50 values of 0.14 ± 0.08 μM, 0.24 ± 0.07 μM and 0.02 ± 0.01 μM, which were 4.6, 1.6 and 473.5 times more active than Foretinib (0.64 ± 0.26 μM, 0.39 ± 0.11 μM, 9.47 ± 0.22 μM), respectively. Structure–activity relationships (SARs) and docking studies indicated that the replacement of phenylpicolinamide scaffold with phenylpyrimidine fragment of the target compounds was benefit for the activity. What's more, the introduction of fluoro atom to the aminophenoxy part played no significant impact on the activity and any substituent group on aryl group is unfavourable for the activity.